Numerical Simulation Study on In-Depth Profile Control of Core–Shell Coagulation System Considering the Time-Variation of Permeability - Zhaobo Sun; Shuchun Cao; Gongchang Wang; Xiaofei Jia; Guoqing Ning (Geofluids)
The coring data in high water-cut oilfields indicates that the reservoir permeability will change continuously with water flooding, while the existing reservoir numerical simulation software cannot consider the time-varying phenomenon of permeability. With the enhancement of reservoir heterogeneity, the near-wellbore profile control fails to stabilize the oil production and control the water cut. The in-depth profile control has been widely used in oilfields as a new technology, and the types of profile control agents are diverse, with a complex mechanism that cannot be effectively described by the existing conventional numerical simulation software. Considering these two phenomena comprehensively, a new three-dimensional, three-phase, six-component mathematical model that can take into account the time-varying phenomenon of reservoir permeability is proposed for a new kind of in-depth profile control system, namely, the core–shell coagulation system, and an integrated numerical simulation software is developed. The mechanism of the in-depth profile control system can be perfectly demonstrated in the simulator with time-variation of permeability. The results of sensitivity analysis show that the effect is influenced by three factors: the mix slug injecting concentration, the coagulant aid slug volume, and the concentration of the suspension dispersing agent.